Nutritional condition and level of maxillary atresia in adolescents - Herrera, Alhi; Cotrado, Sheylla (2022)
This book is an adaptation of a research presented at the Universidad Andina del Cusco, whose objective was to establish the correlation that exists between nutritional status and maxillary atresia. With a quantitative approach, non-experimental, correlational design with transversal temporality. The study population whose random sample was selected 30 children and 30 children in age groups from 10 to 12, 13 and 14 years respectively from the community of Qollana in the district of San Jerónimo (Cusco – Peru). Anthropometric measurements of the body mass index were carried out by measuring weight and height to determine the nutritional status and, in turn, measurements of intercanine and intermolar angles were carried out in study models to determine maxillary atresia for the analysis of results, using the ANOVA and ANOVA test. chi squared with a significance level of 0.05. The results show that regarding the nutritional status with the age, significant differences were found between the female sex (p=0.0130.05). Maxillary atresia was 46.7% female and 51.7% male. No significant differences were found when comparing maxillary atresia between males and females (p = 0.438 > 0.05). It is concluded that by relating the maxillary atresia with the nutritional status in the female sex at 12 years old, there is a relationship with respect to the intermolar angle at 13 and 14 years with respect to the intercanine angle. In the male sex at 13 years old, there is a relationship between both the intercanine and the intermolar and the 14 years only with the intermolar angle in the upper jaw.
Keywords: nutritional status; maxillary atresia